Osteoid osteoma of the mandibular condyle: A diagnostic dilemma - Shameeka Thopte; Namrata Harchandani; Shams Ul Nisa; Rahul Rochani (Wolters Kluwer Medknow Publications, 2018)
Osteoma is benign osteogenic lesions characterized by proliferation of either cancellous or compact bone and can be central, peripheral, or extraskeletal. The most common site is in the skull. When affecting the facial bones, they are frequently found in the mandible, the most common locations being the posterior lingual surface and the mandible angle area. Here, we are presenting a rare case of osteoid osteoma of the mandibular condyle causing facial deformity in a 21-year-old male patient. On investigation, orthopantomogram revealed a solitary ill-defined homogeneous mixed radiopaque-radiolucency with a thin sclerotic border on the left mandibular condyle, cone-beam computed tomography showed a solitary irregular bony multilobulated overgrowth and the fusion imaging of positron emission tomography-computed tomography showed lobulated protuberance along medial margin of the left mandibular condyle with methylene diphosphonate bone scan showed well defined focal increased tracer uptake. The left side condylectomy was performed followed by shaving of inferior border with modified condyle formation by sliding osteotomy. Secondary surgery for correction of occlusion was done, and the patient was advised for orthodontic correction. The present case showed no recurrence after 18 months of follow-up.